Supa Dupa Fly Wimen: Global Perspectives of Women in Hip-Hop - Pineda-Hernández, Inmaculada Concepción (KRK Ediciones, 2009)
Despite its far-reaching effects and transformative impact, hip-hop has not often beeb discussed in Academia, particularly not as an aesthetic movement that encapsulates bell hook's idea of working "from margin to center", providing a voice to the dispossessed. Hip-hop culture has done that in various ways, leaving its imprint on literature, journalism, criticism, performance art and theatre, dance, visual arts, photography, film, video, etc, but it has also been commodified by global corporations, thus losing its originally political purpose. This chapter analyses women's representations in hip-hop culture, and how women develop their own self-representations as a counter effect, and it will illustrate how women in hip hop culture can transform misogynistic representations of female bodies into sites of transgression and creativity.
Keywords: Música; Women in Hip Hop; Women's representations in hip hop culture; Women's self-identifications in hip hop culture